2011
DOI: 10.3109/15563650.2011.590939
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of toxicity ofCleistanthus collinus: Vacuolar ATPases are a putative target

Abstract: Ingestion of Cleistanthus collinus, a shrub native to South India, either intentionally or accidentally, is a common cause of death in the area. Consumption of a boiled decoction of leaves is highly toxic, but medical management of patients is mainly supportive because the molecular mechanisms of toxin action are unknown. Distal renal tubular acidosis is one of the symptoms of poisoning in patients and adenosine triphosphate (ATP) requiring proton pumps is important for acid secretion in the kidney. Hence, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The universal occurrence and persistence of metabolic acidosis and the correlation of metabolic abnormalities to clinical outcome, suggests that renal injury is a significant component of the Cleistanthus Collinus toxicity profile. Toxin mediated inhibition of the vacuolar H + ATPase activity in the renal brush border membrane appears to be the underlying mechanism of injury 14. In animal models it was hypothesized that these toxins caused a depletion/inhibition of thiol/thiol dependent enzymes with subsequent loss of ATPase activity 15.…”
Section: Discussionmentioning
confidence: 99%
“…The universal occurrence and persistence of metabolic acidosis and the correlation of metabolic abnormalities to clinical outcome, suggests that renal injury is a significant component of the Cleistanthus Collinus toxicity profile. Toxin mediated inhibition of the vacuolar H + ATPase activity in the renal brush border membrane appears to be the underlying mechanism of injury 14. In animal models it was hypothesized that these toxins caused a depletion/inhibition of thiol/thiol dependent enzymes with subsequent loss of ATPase activity 15.…”
Section: Discussionmentioning
confidence: 99%
“…One study concluded that the active principles of C. collinus inhibit proton pumps in the renal brush border but does not inhibit the Na + ‐K + pump activity . Another recent experimental study on rats opined that inhibition of vacoular type H + ‐ATPase (V‐ATPase) activity in renal brush border membrane (BBM) is responsible for the development of distal renal tubular acidosis (RTA) and subsequent renal failure .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…One report recommended administration of intravenous neostigmine (0.5 mg) in myasthenic crisis‐like syndrome . Another study opined that therapeutic strategies to bypass the inhibition of vacoular ATPase in the renal BBM would have beneficial effects in the clinical management of these patients .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycosides in Cleistanthus inhibit vacuolar H + ATPase in the renal tubular brush border membrane. These glycosides also deplete glutathione and ATPases in renal cells which may cause oxidation of thiol groups resulting in cellular injury .…”
Section: Introductionmentioning
confidence: 99%